Indonesian Language and Literature Learning Insightful Ecological Intelligence as a Container of Environmental Education - Romi Isnanda; Rio Rinaldi (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
The article discusses the importance of cultivating a human environment. A sense of caring does not appear to be in a person, but through learning and being used to it in life. Efforts to familiarize themselves with the environment should be exalted early through the education level and supported by the family and community environment. One of the subjects that play an important role in cultivating the character of the environment is Indonesian language and literature. Through the teaching of Indonesian language and literature, the teacher packs an insight into ecological intelligence by referring to Mulyasa theory (2013) that one of the 2013 curriculum developments is environmental issues. Furthermore, Theoretical issues and the practice of ecological-oriented learning practices refer to the theory of Suwandi (2019) and Septiaji and Nisya (2020). Based on a description of the Indonesian language and literature study, optmalization of students ' caring for the environment can be carried out well. Keywords: learning, language and literature, ecological intelligence Abstrak Artikel membahas permasalahan pentingnya menanamkan sikap peduli terhadap lingkungan bagi manusia. Rasa kepedulian tidak muncul begitu saja dalam diri seseorang, melainkan melalui pembelajaran dan membiasakannya dalam kehidupan. Upaya membiasakan kepedulian terhadap lingkungan harus dimulia sejak dini melalui jenjang pendidikan dan didukung oleh lingkungan keluarga dan masyarakat. Salah satu mata pelajaran yang berperan penting dalam menanamkan karakter peduli terhadap lingkungan adalah bahasa dan sastra Indonesia. Melalui pengajaran bahasa dan sastra Indonesia, guru mengemas bahan ajar berwawasan kecerdasan ekologis dengan mengacu pada teori Mulyasa (2013) bahwa salah satu pengembangan kurikulum 2013 adalah permasalahan lingkungan hidup. Selanjutnya, permasalah secara teorEtis dan praktik pelaksanaan pembelajaran berwawasan ekologis mengacu pada teori Suwandi (2019) dan Septiaji dan Nisya (2020). Berdasarkan uraian tentang pembelajaran bahasa dan sastra Indonesia berwawasan ekologis, optmalisasi penanaman karakter kepedulian siswa terhadap lingkungan dapat terlaksana dengan baik. Kata kunci: pembelajaran, bahasa dan sastra, kecerdasan ekologis